(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The article is devoted to the problem of the school pupils intellective development with the modern learning technologies. In this article are geveng the short characteristics such technologies as "Student Team Learning", "Project Technology", "Play Language Portfolio".